Artificial Intelligence In Learning English for Students of STIKOM Uyelindo Kupang - Heni, Heni (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2025)
This research purpose is to compare the opportunities and challenges in using AI in English learning.  The scope of the study is limited to the opportunities and challenges of English language learning. This study was conducted using a mixed method of observing and distributing questionnaires to students. AI has transformed English language learning in higher education. Students use AI for a variety of purposes, asking and solving questions and checking grammatical errors, checking plagiarism, paraphrasing, and reviewing literature. This research also reveals that AI has various advantages for language teaching and learning, including the detection of plagiarism and grammatical errors. Additionally, AI has created opportunities and challenges for the future of English language teaching. This research is expected to find out what opportunities and challenges exist in using AI in learning English for STIKOM Uyelindo Kupang students. The contributions of this research are strengthening technology-based learning theory, demonstrating how AI can transform traditional approaches into adaptive and personalized learning, and become new learning models: Generating integrative models of linguistic theory, pedagogy, and artificial intelligence (e.g., AI-assisted language learning models). Learning behavior analysis: providing new insights into how students interact with AI systems, for example, in terms of motivation, learning autonomy, or learning strategies.